STRATEGI CITY BRANDING OLEH PEMERINTAH DAERAH KABUPATEN SIAK DALAM PENINGKATAN DAYA TARIK PARIWISATA - Rusadi, Sylvina; Wedayanti, Made Devi (UIR PRESS, 2019)
City Branding is a promotion strategy to increase the attractiveness of tourism which is very popular lately, as evidenced by various regions in Indonesia trying to shape the character of their regional tourism so that it can be more easily recognized only through a term. The Siak Regency Government also utilizes City Branding as one of the promotion strategies in increasing the attractiveness of its regional tourism, namely through